(untitled) (Annals of Bangladesh Agriculture, 2020)
The study was conducted to evaluate the potentiality of potato as an alternative source of carbohydrate in fish feed and its effect on the growth performance, glucose level and survivability of tilapia (Oreochromis niloticus). The experiment was designed into four treatments with three replications in each including control T1 (feed without rice bran and potato), T2 (feed with rice bran), T3 (feed with raw potato) and T4 (feed with boiled potato). Tilapia fry (average 6.27±0.07 g) were randomly distributed in each treatment as 40 fish per 300L tank and feed with experimental diets (protein 35%). Significantly higher (P<0.05) survival rate of the fishes were observed in T4 (85%) followed by T2 (72.5%), T3 (57.5%) and T1 (47.5%). Feed conversion ratio (FCR) was significantly lower in T4 (2.76) compared to T2 (2.89) T3 (3.2) and T1 (3.93). Specific growth rate (SGR) was significantly higher (P<0.05) in T4 (3.11%) followed by T2 (2.94%), T3 (2.85%) and T1 (2.68%). Higher (P<0.05) condition factor (CF) was also observed in T4 (3.19) compared to T2 (2.85), T3 (2.77) and T1 (2.64). Higher glucose level was found in T4 (P<0.05) compared to T2, T3 and T1. The water quality parameters such as temperature, dissolved oxygen (DO), pH, ammonia, nitrate, nitrite and phosphate were not significantly (P>0.05) differed among the treatments. The results indicated that boiled potato treated feed would be effective as energy rich growth promoter in tilapia culture. However, further investigation is needed in farm condition adding varying levels of potato in feed. Ann. Bangladesh Agric. (2019) 23(1) : 79-89